2021
DOI: 10.1002/cjce.23992
|View full text |Cite
|
Sign up to set email alerts
|

CO2 reforming of methane over the growth of hierarchical Ni nanosheets/Al2O3‐MgO synthesized via the ammonia vapour diffusion impregnation

Abstract: A novel ammonia vapour diffusion-assisted impregnation technique was developed to synthesize the Al 2 O 3 -MgO-supported hierarchical Ni nanosheets. The resulting catalysts with different times for ammonia vapour treatments (at 12, 18, and 20 hours) were prepared to investigate the growth of Ni nanosheets on the catalyst surface. All catalysts were tested for CO 2 reforming of methane and a comprehensive characterization study was conducted by XRD, N 2 adsorption-desorption, H 2 -TPD, H 2 -TPR, CO 2 -TPD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…For instance, a series of Ni nanosheets (NS) supported on Al 2 O 3 À MgO mixed oxides were synthesized by ammonia vapour diffusion-assisted impregnation technique. [276] After 12-h ammonia diffusion into the Ni nitrate precursor, α-Ni(OH) 2 nanosheets were formed from the reaction between Ni ions and hydroxide ions. This structure exhibited the highest total basicity (0.77 mmol/g) with a large percentage of strong basic sites (0.33 mmol/g), which effectively gasified the carbon species by the oxygen and hydroxide ions dissociated from adsorbed CO 2 .…”
Section: Treatment Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a series of Ni nanosheets (NS) supported on Al 2 O 3 À MgO mixed oxides were synthesized by ammonia vapour diffusion-assisted impregnation technique. [276] After 12-h ammonia diffusion into the Ni nitrate precursor, α-Ni(OH) 2 nanosheets were formed from the reaction between Ni ions and hydroxide ions. This structure exhibited the highest total basicity (0.77 mmol/g) with a large percentage of strong basic sites (0.33 mmol/g), which effectively gasified the carbon species by the oxygen and hydroxide ions dissociated from adsorbed CO 2 .…”
Section: Treatment Parametersmentioning
confidence: 99%
“…Apart from the treatment temperature, the duration is another determining factor for total basicity and basic site distribution of catalysts. For instance, a series of Ni nanosheets (NS) supported on Al 2 O 3 −MgO mixed oxides were synthesized by ammonia vapour diffusion‐assisted impregnation technique [276] . After 12‐h ammonia diffusion into the Ni nitrate precursor, α‐Ni(OH) 2 nanosheets were formed from the reaction between Ni ions and hydroxide ions.…”
Section: Optimization Of Surface Acidity/basicity Of Al2o3‐based Meta...mentioning
confidence: 99%
“…Our group has developed a novel ammonia vapor diffusion impregnation method that allows the size of the hierarchical nanostructures of the modified catalyst surface to be controlled by the ammonia vapor diffusion time. Previously, the hierarchical structure and basicity of the layered nanosheets on 10 wt% Ni/MgO-Al 2 O 3 prepared by ammonia vapor diffusion impregnation for 20 h exhibited that the hierarchical nanostructures on the surface can enhance CO 2 adsorption–dissociation and prevent coke formation for the CRM process [ 19 ]. A 10 wt% Ni-1 wt% ZrO 2 /Al 2 O 3 catalyst prepared by a similar method with an ammonia diffusion time of 6 h demonstrated an improvement in the steam activation–dissociation and coke resistance for the combined steam and CO 2 reforming of methane (CSCRM) process operated under low-temperature and low-steam conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Dharmasaroja et al revealed preparation of hierarchical Ni layered hydroxide via novel ammonia vapor diffusion impregnation. The advantages of the ammonia vapor diffusion impregnation method comprise low temperature and cost saving . The hierarchical Ni nanosheet catalyst represented the metal dispersion, surface interaction, and the basicity of the catalyst surface, improving the catalytic activity especially CO 2 adsorption-dissociation in the CO 2 reforming of methane. Nevertheless, hierarchical Ni-based catalysts have been rarely studied for CSCRM reaction …”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art for our design included the well-dispersed Ni nanoparticles accompanied by the superior selectivity toward oxygenated reactants resulting from the morphology and components. Thus, the hierarchical nanosheet of Ni-ZrO 2 supported on Al 2 O 3 catalysts (the 10Ni-1ZrO 2 /Al 2 O 3 ( x h), also called as the treated catalyst) containing 10 wt % Ni and 1 wt % ZrO 2 was prepared by our ammonia vapor diffusion impregnation 25 with various diffusion times ( x h = 1, 6, and 12 h). The difference of times for ammonia vapor treatment can be attributed to the change in size as well as the dispersion of hierarchical Ni-ZrO 2 nanosheets on the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%